2021
DOI: 10.31051/1852.8023.v13.n3.35049
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Cricothyroidotomy Procedure: Lecture on Surgical Anatomy and Briefing of the Procedure Followed by Skill Assessment in First Semester Medical Students

Abstract: Introduction: Emergency Cricothyroidotomy (ECT) is a life-saving procedure where the cricothyroid membrane is incised to access the larynx to establish breathing in ‘can’t intubate, can’t ventilate’ situations. This procedure can be taught along with midline neck anatomy to the first semester medical students and their understanding and application of knowledge could be assessed on cadavers. Materials and methods: Total three sessions was organized to expose and assess the first semester medical students about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A cricothyrotomy procedure would need a simple blade; as a result, it can be completed without wasting time. 30 The time of full oxygen saturation reported for cricothyrotomy was 3 minutes. A study by Chen et al showed that SpO2 was increased postoperatively, reaching 95% at 12 seconds, 131 seconds, and 144 seconds in the cricothyroid membrane puncture guided tracheostomy (CMPGT), surgical cricothyroidotomy (SC) and Griggs guidewire dilating forceps (GWDF) groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cricothyrotomy procedure would need a simple blade; as a result, it can be completed without wasting time. 30 The time of full oxygen saturation reported for cricothyrotomy was 3 minutes. A study by Chen et al showed that SpO2 was increased postoperatively, reaching 95% at 12 seconds, 131 seconds, and 144 seconds in the cricothyroid membrane puncture guided tracheostomy (CMPGT), surgical cricothyroidotomy (SC) and Griggs guidewire dilating forceps (GWDF) groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A cricothyrotomy procedure would need a simple blade; as a result, it can be completed without wasting time. 30 The time of full oxygen saturation reported for cricothyrotomy was 3 minutes. A study by Chen et al .…”
Section: Discussionmentioning
confidence: 99%